Characterization of concurrent ku band tropospheric scintillation and rain attenuation in Malaysia - Ibtihal Fawzi Elshami; Jafri Din; Lam Hong Yin; Ali I Elgayar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Tropospheric scintillation in satellite communication systems operating at frequencies over 10 GHz is a significant impairment, especially in tropical regions, as attenuation affects scintillation dramatically. This work concentrates on tropospheric scintillation in equatorial Johor Bahru, Malaysia, based on a one-year Ku-band propagation measurement study utilising a direct broadcast receiver and an automatic weather station. This study aimed to investigate the relationship between wet scintillation and rain attenuation using experimental measurements. The power spectral analysis has been carried out to determine required cut-off frequency of filtering to separate out rain attenuation and scintillation effects. The results can provide significant information on the fluctuations of wet scintillation at Ku-band earth space link in tropical regions.